2014
DOI: 10.1089/g4h.2014.0026
|View full text |Cite
|
Sign up to set email alerts
|

Gaming and Conventional Exercises for Improvement of Arm Function After Stroke: A Randomized Controlled Pilot Study

Abstract: The present randomized controlled pilot study showed that both arm and hand function improved as much after training with a rehabilitation game as after time-matched conventional training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…This included seven studies [ 21 , 44 , 53 , 74 , 76 , 86 , 91 ] (21%) conducted during the sub-acute (≤ three months) stage (range 1.9–10.3 weeks, M = 3.86 weeks, SD = 3.23), while the remainder completed VR interventions during the chronic (> 3 months post-stroke) stage (range 17.2–427.8 weeks, M = 127.40 weeks, SD = 132.5). Seventeen studies [ 13 , 21 , 53 , 57 , 74 , 77 , 79 – 82 , 85 , 87 , 91 , 92 , 94 ] included both ischemic and hemorrhagic stroke patients, three included only ischemic stroke patients [ 78 , 86 , 93 ], and 11 did not report specific details about stroke type. Only three studies [ 21 , 74 ] reported data on stroke severity, two utilizing the National Institutes of Health Stroke Scale (NIHSS) and one study [ 86 ] used the Canadian Neurological Scale of Stroke Severity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included seven studies [ 21 , 44 , 53 , 74 , 76 , 86 , 91 ] (21%) conducted during the sub-acute (≤ three months) stage (range 1.9–10.3 weeks, M = 3.86 weeks, SD = 3.23), while the remainder completed VR interventions during the chronic (> 3 months post-stroke) stage (range 17.2–427.8 weeks, M = 127.40 weeks, SD = 132.5). Seventeen studies [ 13 , 21 , 53 , 57 , 74 , 77 , 79 – 82 , 85 , 87 , 91 , 92 , 94 ] included both ischemic and hemorrhagic stroke patients, three included only ischemic stroke patients [ 78 , 86 , 93 ], and 11 did not report specific details about stroke type. Only three studies [ 21 , 74 ] reported data on stroke severity, two utilizing the National Institutes of Health Stroke Scale (NIHSS) and one study [ 86 ] used the Canadian Neurological Scale of Stroke Severity.…”
Section: Resultsmentioning
confidence: 99%
“…Tabletop systems involved multitouch display technologies (e.g. [ 92 , 94 ]), requiring finger touch response [ 94 ] or the manipulation of tangible user interfaces. CG therapies included Wii (Nintendo [ 73 , 74 , 80 , 83 , 86 , 91 ]), Xavix [ 83 ], EyeToy (PlayStation [ 88 ]), IREX system [ 53 , 82 , 97 ], Xbox Kinect [ 81 , 89 ], or a combination of systems [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reaching scores (n = 10) in this game were measured using the Action Research Arm test and the Fugl-Meyer assessment and then compared with scores from another trial conducted simultaneously using time-matched traditional methods (n = 10). Although the action research arm scores were slightly higher in the FurballHunt group, the authors found no significant differences between the two groups (Kottink et al, 2014).…”
Section: Stroke Rehabilitationmentioning
confidence: 78%
“…Finally, a study was conducted utilizing the game Furball-Hunt, which is based on teaching players upper extremity motor skills (Kottink, Prange, Krabben, Rietman, & Buurke, 2014). This re-learning technique challenged players to direct their reaching movements with the affected arm and hand on a horizontally placed screen.…”
Section: Stroke Rehabilitationmentioning
confidence: 99%
“…Clinical utility of serious video games (e-therapies or therapeutic games) has been studied in patients with various chronic conditions including depression, Parkinson’s disease, asthma, diabetes, cancer, or stroke (2226). Table S1 in Supplementary Material provides examples of mobile apps and games for the treatment of depression, anxiety, dementia, pain, attention deficit hyperactivity disorder (ADHD), and cerebral palsy.…”
Section: Introductionmentioning
confidence: 99%